Revisiting Money-Price Relationship in Nepal Following a New Methodological Framework - Shrestha, Min Bahadur; Bhatta, Guna Raj (NRB Economic Review, 2018)
Information on the pattern of money-price relationship is crucial for formulating appropriate monetary policy and implementing it effectively. This paper re-examines the money-price relationship in Nepal following a new methodological framework for time series data analysis. Test results show that money supply significantly affects domestic price in Nepal. Indian inflation is the major factor that has largest impact on the price situation in Nepal. However, exchange rate is not found to be associated with the changes in price level in Nepal. Test results also show that money-price relationship in Nepal has become much stronger in the recent times in terms of the magnitude of impact.